Seasonal trends in ear, nose, throat and head, neck patients undergoing shortwave diathermy at a tertiary care centre of Punjab: a five-year study - Munjal, Manish; Teotia, Avkash; Kaur, Jatinder; Rishi, Porshia; Sidhu, Harjinder; Munjal, Shubham; Verma, Hitesh (International Journal Of Community Medicine And Public Health, 2020)
Background: Shortwave diathermy, a therapeutic modality in acute inflammatory conditions of the ear, nose and neck has its utility in the paediatric, adolescent, middle age and the elderly. The seasonal variations of the patients enrolled in physiotherapy clinics for temporo-fascio-cervical diathermy sessions during a 5 years period, were analysed. Methods: 490 patients with inflammatory pathologies localized to the head and neck region and referred to the physiotherapy unit of a tertiary care centre of Punjab were analysed. All were subjected to shortwave diathermy. The subjects were analysed for any seasonal trends. Results: In the paediatric age group, maximum patients were observed in the month of March over the period of 5 years followed by the month of January. In the adolescent population maximum patients were observed in the month of November over the period of 5 years followed by the month of December. In the Adult population maximum patients were observed in the month of April over the period of 5 years followed by January and August. Conclusion: Paediatric patients came for regular sittings in the end of March end, i.e. post examination vacation period. The elderly visited mostly during winters. Malignant otitis externa with underlying diabetes worsens in winters due to increase in intake of sugary energy drinks.